What is Green? A Case on Selected Companies - Dwi Hayu Agustini, M Y; Bekti Retnawati, B; Suciarto Athanasius, S (KnE Social Sciences, 2018)
More companies are going green. They believe that greening the business is their responsibility and is simply the right thing to do. It benefits not only the company but also the consumers. Since the substance of the green business concept is rather ambiguous, it is difficult to evaluate whether a green claim is correct and is not a greenwash. The study tries to find out the understanding of companies conducting green practices on green business. It aims specifically to explore to what extent they know about green business and whether their practices are accordingly green. It is a case study on three Indonesian companies identified as conducting green practices. Data were gathered through interviews of the owner-manager or the representative of the companies. The study shows that the understanding on green business still varies and reasons underlying their green practices are commitment of not to harm the environment. In the beginning, they did not realize if what they have done are green practices. Knowing the benefits of being green can be the motivation for being green. Disseminating the laws is thus important. Keywords: green business, green practice, green claim, green product, Indonesia